KEDUDUKAN HUKUM PERJANJIAN UTANG-PIUTANGDI BALIK PERJANJIAN PENGIKATAN JUAL BELI - Christopher Nicolas Cowandy (Institut Pendidikan Tapanuli Selatan, 2021)
Over the past few years in Indonesia, there has been a phenomenon which happened among the citizens regarding agreements that they made in front of the notary. The parties involved made a private deed of a Debt Agreement and the debtor agrees to warrant their assets, including land or buildings as a security to the creditor by doing a Sale and Purchase Deed legally in front of the notary. The problems arise when the creditor made a right transfer of the land certificate at the National Land Agency without the knowledge and approval of the debtor. This research was conducted to see if the Sale and Purchase Deed that has been done as a security in front of the notary is legitimate if there was a privately made deed of a Debt Agreement that has been made before, and what is the legal standing of this agreement. The method use for this research is a normative juridical method which is a method of researching the constitutions and library materials, collect and analyze the data and draw a conclusion with a deductive thinking. The result of this research is expected to be a way to gain an understanding of the legal validity and certainty of the Sale and Purchase Deed that has been used as a security for a privately made deed of a Debt Agreement.